2000
DOI: 10.1097/00004647-200003000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Posttraumatic Hypothermia and Hyperthermia on the Inflammatory Response after Fluid Percussion Brain Injury: Biochemical and Immunocytochemical Studies

Abstract: The purpose of this study was to investigate: 1) the temporal and regional profile of polymorphonuclear leukocyte (PMNL) infiltration after moderate traumatic brain injury using the parasagittal fluid percussion model and 2) the effects of posttraumatic hypothermia (30 degrees C) and hyperthermia (39 degrees C) on the acute and subacute inflammatory response. We hypothesized that posttraumatic hypothermia would reduce the degree of PMNL accumulation whereas hyperthermia would exacerbate this response to injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(93 citation statements)
references
References 93 publications
5
88
0
Order By: Relevance
“…Hypothermia (301C) also provided protection against secondary posttraumatic injury associated with hypotension and hypoxia (Yamamoto et al, 1999). Posttraumatic hypothermia (301C) reduced and hyperthermia (391C) increased the inflammatory response to FPI in rats (Chatzipanteli et al, 2000). Moderate hypothermia (301C) after TBI reduced posttraumatic dysfunction of the blood-brain barrier (Jiang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia (301C) also provided protection against secondary posttraumatic injury associated with hypotension and hypoxia (Yamamoto et al, 1999). Posttraumatic hypothermia (301C) reduced and hyperthermia (391C) increased the inflammatory response to FPI in rats (Chatzipanteli et al, 2000). Moderate hypothermia (301C) after TBI reduced posttraumatic dysfunction of the blood-brain barrier (Jiang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective strategies, including antibody treatments and therapeutic hypothermia, have been reported to decrease the acute inflammatory response and lead to histopathological protection (Carlos et al, 1997;Chatzipanteli et al, 2000). However, a recent review by Emerich and colleagues (2002) concluded that no study has successfully demonstrated that leukocytes satisfy any criteria for causing cell death or increased infarction due, in part, to a lack of sufficient controls.…”
Section: Inflammationmentioning
confidence: 99%
“…The mechanisms underlying the beneficial effects of posttraumatic hypothermia are multifactorial and include excitotoxicity, calciumdependent intercellular signaling, apoptosis, and edema formation (Dietrich and Bramlett, 2010;Yenari and Han, 2012). In addition, hypothermia has been reported to attenuate various inflammatory events including proinflammatory gene expression and protein levels when compared with normothermic TBI in some (Chatzipanteli et al, 2000;Goss et al, 1995;Kinoshita et al, 2002;Lotocki et al, 2006;Marion et al, 1997;Vitarbo et al, 2004;Whalen et al, 1997) but not all studies (Buttram et al, 2007;Truettner et al, 2005). Thus, a current area of research is directed to the continued investigation of the cellular and molecular events associated with the beneficial effects of hypothermia on posttraumatic inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%